A Management Model of Competency-Based Block System Automotive Learning - Supraptono, Supraptono; Rusdarti, Rusdarti; Soesanto, Soesanto; Prihatin, Titi (The Journal of Educational Development, 2019)
For students graduating from the automotive engineering education study program, this study aims to (1) determine a competency-based block system practice learning management model to improve the students’ skills; (2) to implement the competency-based block system practice learning management model; (3) to know the level of effectiveness of the model. This research implemented a research and development (R&D) approach including (1) preliminary studies including needs and contents analyses, (2) development including design, implementation and evaluation, and (3) testing the effectiveness of the product as a semi-summative evaluation. The data for this study were drawn using interview, documentation, observation, and questionnaires. The data were validated by testing their reliability and validity. The data were then analyzed using descriptive percentages and quantitative models. The results of the subsequent analyses were transformed into constructs of percentages of feasibility in the implementation of practical learning activities. The results of the study show that (1) the factual model has not been equipped with an analysis of the basic needs of practice, the formulation of objectives of the block practice, the design of the practice program, the implementation of the practice program, and the evaluation of the block practice programs so that the student’s proficiency level is still low; (2) the results of the validation from management experts and FGD indicate that the conceptual model of learning is feasible to be applied in learning activities; (3) after going through various suggestions and improvements to the hypothetical model it proved to be feasible to apply in learning. The model of automotive learning systems is very effective and easy to implement.